Agronomic evaluation of sugarcane (Saccharum spp. hybrid) genotypes forits cane yield and quality under different fertilizer levels - Tayade, Arjun S; Ponnaiyan, Geetha; S, Anusha; Palaniswami, C; Govindaraj, P (Journal of Sugarcane Research, 2024)
An experiment was conducted during 2021-22 to evaluate the performance of early maturing high yielding sugarcane varieties at ICAR-Sugarcane Breeding Institute, Coimbatore. The experiment was planted in split plot design and replicated twice. Seven elite sugarcane genotypes Co 11015, Co 15005, Co 15006, Co 15007, Co 15009, Co 15010, Co 15021 were assessed agronomically with three standards checks i.e. Co 09004, Co 86032 and CoC 671 and two fertilizer levels i.e. 100 and 125 % RDF. The experiment was planted in wide row spacing (150 cm). The crop was harvested at 12th month and observation on NMC, cane height, cane girth, number of nodes, cane weight and cane yield per plot was recorded. Cane yield was inﬂuenced signiﬁcantly due to diﬀerent elite genotypes wherein, elite sugarcane genotypes, Co 15010 (139.79 t/ha) recorded signiﬁcantly higher cane yield than the standards Co 86032 (114.85 t/ha), Co09004 (108.74 t/ha) and CoC 671(94.20 t/ha). Juice quality (Brix, sucrose, purity and CCS percent) were studied at harvest with random cane samples. Juice qualities were not inﬂuenced signiﬁcantly due to fertilizer levels; however juice Brix, Sucrose%, Purity % and CCS % at harvest showed signiﬁcant varietal diﬀerences.